The Role of Circular RNAs in the Carcinogenesis of Bladder Cancer - Ghafouri-Fard, Soudeh; Najafi, Sajad; Hussen, Bashdar Mahmud; Basiri, Abbas; Hidayat, Hazha Jamal; Taheri, Mohammad; Rashnoo, Fariborz (Frontiers in Oncology, 2022)
Circular RNAs (circRNAs) are a group of transcripts with enclosed configuration which can regulate gene expression. These transcripts have important roles in normal development and in the pathogenesis of disorders. Recent evidence has supported involvement of circRNAs in the development of bladder cancer. Several circRNAs such as circ_0058063, hsa-circRNA-403658, circPDSS1, circCASC15, circRNA-MYLK and circRNA_103809 have been up-regulated in bladder cancer samples. On the other hand, hsa_circ_0137606, BCRC-3, circFUT8, hsa_circ_001598, circSLC8A1, hsa_circ_0077837, hsa_circ_0004826, circACVR2A are among down-regulated circRNAs in bladder cancer. Numerous circRNAs have diagnostic or prognostic value in bladder cancer. In this review, we aim to outline the latest findings about the role of circRNAs in bladder cancer and introduce circRNAs for further investigations as therapeutic targets.